KARAKTERISASI ISOLAT RHIZOCTONIA MIKORIZA PADA ANGGREK PHALAENOPSIS AMABILIS - Soelistijono, Soelistijono; UTAMI, DWI SISILO; Priyatmojo, Achmadi (JURNAL ILMIAH AGRINECA, 2012)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–>Mycorrhizal Rhizoctonia is a fungus that capable to associate with Phalaenopsis amabilis orchid. This study was aimed to characteristic mycorrhizal Rhizoctonia that associated with P. amabilis orchid in morphology. The results showed that colony colour, cell lenght and nucleus number a several isolates of mycorrhizal Rhizoctonia on P. amabilis had no differences, but had differences on cell thickness and isolate grouping based on hyphal anastomosis test<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>